Culture of Chlorella ellipsoidea (Gerneck) in Supernatant of Different Concentrations of Digested Waste Potato Powder - Habib, M. A. B.; Uddin, M. M.; Nur, N. N.; Parvin, M. (Biological Sciences - PJSIR, 2007)
. The growth performance of Chlorella ellipsoidea was eval uated i n supernatants of different concentrations of digested waste potato powder (DWPP) medi um, Bold basal medi um (BBM) as control and tap-water (TW) wi thout added n utrient i n the laboratory for th ree months. Three different amounts of waste potato powder such as 0.80, 1 .00 and 1 .20 g/ 1 were allowed to digest for I O days to get clear supernatant. The i nitial cell density of C. ellipsoidea was2.5 x I05 per ml which attai ned a maximum density of 227.45 x I05 cell/ml in BBM , 220x I05 cell/ml i n supernatant of 0.80 g DWPP/ 1 followed by I87.33 x I05 cell/ml i n supernatant of 1 .00 g DWPP/1 and I58.67 x I05 cell/ml in superna tant of 1 .20 g DWPP/ 1 and 126.823 x I 05 cell/ml in tap-water without added n utrien t. Similar trend was observed i n the cases of chlorophyll .l! of th is microalga and optical density of media containi ng C. ellipsoidea . The prox i mate compo sition of waste potato powder was found to contai n (on dry matter basis) 8.67% moisture , 1 3.31 % crude protein , 1 .60% crude lipids and 4.55% ash. C. ellipsoidea grown in various concentrations of DWPP, TW and BBM was analyzed and it was found that th e amount of moisture , crude protein , crude l ipids and ash varied from 7. 1 5 to 8.00%,23.4 to 48.11 %, 8.63 to 1 4.23%, and 2.66 to 4.05%, respectively. Cell n umber of C. ellipsoidea was significantl y (p<0.05) higher when grown i n supernatant of 0.80 g/ 1 DWPP than i n supernatant of other concentrations of DWPP, TW and BBM. Chlorophyll .l! of C. ellipsoidea and optica l density of culture media of three concentrations of DWPP,TW and BBM followed almost similar trend. However, cell number was significantl y (p < 0.05) correlated with chlorophyll _!! (r = 0.965).